Capitania do Espírito Santo uma feitoria portuguesa no Atlântico Sul: a pauta de comércio e a atividade mercantil (1600-1642) - Vitória Sobrinho, Sueni da (2013)
In this dissertation we did propose to perform a historiographical analysis of the Portuguese’s treasury administration regarding the economic dynamics of the Espirito Santo’s Captaincy, in the chronological cut proposed [period 1600-1642]. Thus, we expect demonstrate if the depressed character of the Espirito Santo’s Captaincy economy is linked to the smuggling, the misdirections and the absenteeism of donees whose the last presence occurred from 1609 to 1627. Our analysis is assumed to emerge the local interest in maintaining the privileges of trade and political power in a network qualified as the economy of the common-good and the participation of Espirito Santo’s captaincy in the economic juncture (1600-1642), describing the agenda of exportation and importation of products, the business relationship with the adjacent captaincies and examining the ways of payment and accumulation of the productive structure of the captaincy.